Tipologi Penindakan Kejahatan Korporasi Dalam Korupsi Dana Bantuan Pandemi Covid-19 - Kristina, Michelle (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2021)
The development of human life nowadays cannot be separated from various aspects such as economy, politics, and technology, including the impact of the coronavirus outbreak (Covid-19 or SARS-CoV-2) which emerged at the end of 2019. Responding to this Covid-19 pandemic outbreak In Indonesia, the government has issued various policies as measures to prevent and handle the spread of Covid-19. One of these policies is to limit community activities. These restrictions have implications for the fulfilment of the economic needs of the affected communities. Responding to the urgency of this community's economic situation, the government held a social assistance program as a measure to ease the community's economic burden. However, the procurement of the program was used as a chance for corruption involving the Ministry of Social Affairs and corporations as the winning bidders. This study uses a qualitative methodology with a normative juridical approach and literature. The approach is carried out by conducting a juridical analysis based on a case approach. The results of the study show that the corporations involved cannot be separated from corporate responsibility. However, the criminal liability process against the corporation is deemed not to reflect justice for the current situation of Indonesia is experiencing. The crime was not carried out in a normal situation but in a situation when Indonesia was trying hard to overcome the urgent situation, the Covid-19 pandemic. Corporate crimes committed by taking advantage of the pandemic situation are deemed necessary to prioritize special action or the weight of criminal acts committed by corporations. The weighting of criminal sanction is the right step as a law enforcement process for corporate crimes during the pandemic.